Increase in pea productivity associated with irrigation management - Santos, Osvaldir F. [UNESP]; Cunha, Fernando F.; Taira, Tiago L.; Souza, Epitácio J. [UNESP]; Leal, Aguinaldo J. F. (FapUNIFESP (SciELO), 2018)
Proper irrigation management is crucial to obtain high yields of pea, since its cultivation is recommended in cold and dry seasons. Taking into account the great genetic diversity, we considered necessary to evaluate cultivars which best adapt to the intrinsic conditions of Cerrado Region, as it presents low fertility soil, long dry period in the winter, drought periods (veranicos) in rainy season, mainly in January and February (summer). Thus, the aim of this study was to evaluate adaptability of green-pea cultivars under different irrigation depths in Northeast Region of state of Mato Grosso do Sul. The experiment was installed in a split plot scheme, with four irrigation depths [50, 75, 100 and 125% of crop evapotranspiration (ETc)] and at subplots, four pea cultivars (Forró, Frevo, Pagode and Samba) in a randomized block design with three replications. Pod length, number and mass of grains per pod, number of pods per plant, plant length, productivity and efficiency of water use were evaluated. Excess water supply (water stress) or shortage (water deficit) can cause decrease in the productivity of pea crop for green grains, considering replacement of 114.81% of Etc, the most recommended for the crop. Cultivar Forró, showed the best productive performance in relation to other cultivars, in the climatic conditions of Southern Cerrado (Mato Grosso do Sul, Brazil).
Aumento da produtividade de ervilha associado ao manejo da irrigação
Keywords: Edaphoclimatic adaptability; Pisum sativum; Water deficit